PENETAPAN KADAR VITAMIN C DENGAN SPEKTROFOTOMETRI UV-Vis PADA BERBAGAI VARIASI BUAH TOMAT - Asiska Permata Dewi (JURNAL FARMASI DAN MAKANAN, 2018)
Tomato is a kind of fruit containing vitamin C. Vitamin C is needed for collagen production, bone and teeth formation, wound healing, and immunity to infection. This vitamin is dissolve in water and easy to be destroyed by light and high temperature, so the storage and condition of tomato fruits need special attention to keep an adequate vitamin C level it contained. This research aimed to determine the level of vitamin C in three kinds tomato fruits maturation degree: raw, half-mature, and mature. The quantification was conducted using spectrophotometry UV-Vis method with maximum wave length of 265 nm and absorbance of 0.475 (Y=0.0557X + 0.0789). The result showed that the average level of vitamin C in raw, half-mature, and mature tomato was 74.03666; 53.81333; and 43.56666 mg/100g, respectively. In conclusion, the level of vitamin C in raw tomato was the highest among all samples.